Effect of Salicylate on KCNQ4 of the Guinea Pig Outer Hair Cell - Wu, T. (American Physiological Society, 2010)
Salicylate causes a moderate hearing loss and tinnitus in humans at high-dose levels. Salicylate-induced hearing loss has been attributed to impaired sound amplification by outer hair cells (OHCs) through its direct action on the OHC motility sensor and/or motor. However, there is a disparity of salicylate concentrations between the clinical and animal studies, i.e., extremely high extracellular concentrations of salicylate (from 1 to 10 mM) is required to produce a significant reduction of electromotility in animal studies. Such concentrations are above the clinical/physiological range for humans. Here, we showed that clinical/physiological concentration range of salicylate caused concentration-dependent and reversible reductions in I(K,n) (KCNQ4) and subsequent depolarization of OHCs. Salicylate reduced the maximal tail current of the activation curve of I(K,n) without altering the voltage-sensitivity (V(half)). The salicylate-induced reduction of I(K,n) was almost completely blocked by linopirdine (0.1 mM) and BaCl(2) (10 mM). Consistent with the finding in OHCs, salicylate significantly reduced KCNQ4-mediated current expressed in Chinese hamster ovarian (CHO) cells by comparable amplitude to OHCs without significantly shifting V(half). Nonstationary fluctuation analysis shows that salicylate significantly reduced the estimated single-channel current amplitude and numbers. Intracellular Ca(2+) elevation resulting from cytoplasmic acidosis also contributes to the current reduction of I(K,n) (KCNQ4) of OHCs. These results indicate a different model for the salicylate-induced hearing loss through the reduction of KCNQ4 and subsequent depolarization of OHCs, which reduces the driving force for transduction current and electromotility. The major mechanism underlying the reduction of I(K,n) (KCNQ4) is the direct blocking action of salicylate on KCNQ4.